Internal structure of the fly elementary motion detector - Eichner, Hubert; Maximilian Jösch; Schnell, Bettina; Reiff, Dierk F; Borst, Alexander (Neuron)
Recent experiments have shown that motion detection in Drosophila starts with splitting the visual input into two parallel channels encoding brightness increments (ON) or decrements (OFF). This suggests the existence of either two (ON-ON, OFF-OFF) or four (for all pairwise interactions) separate motion detectors. To decide between these possibilities, we stimulated flies using sequences of ON and OFF brightness pulses while recording from motion-sensitive tangential cells. We found direction-selective responses to sequences of same sign (ON-ON, OFF-OFF), but not of opposite sign (ON-OFF, OFF-ON), refuting the existence of four separate detectors. Based on further measurements, we propose a model that reproduces a variety of additional experimental data sets, including ones that were previously interpreted as support for four separate detectors. Our experiments and the derived model mark an important step in guiding further dissection of the fly motion detection circuit.

Solid-state NMR measurements of asymmetric dipolar couplings provide insight into protein side-chain motion - Schanda, Paul; Huber, Matthias; Boisbouvier, Jérôme; Meier, Beat H.; Ernst, Matthias (Angewandte Chemie International Edition)
Nonsymmetric motion: Solid‐state NMR measurements of dipolar coupling tensors provide insight into protein dynamics. The hitherto ignored asymmetry of the dipolar coupling tensor contains valuable information about motional asymmetry, which was used in the first direct site‐resolved measurement of such tensors. Important motions such as rotamer jumps can now be directly detected in the solid state.

Three-dimensional deuterium-carbon correlation experiments for high-resolution solid-state MAS NMR spectroscopy of large proteins - Lalli, Daniela; Schanda, Paul; Chowdhury, Anup; Retel, Joren; Hiller, Matthias; Higman, Victoria A.; Handel, Lieselotte; Agarwal, Vipin; Reif, Bernd; van Rossum, Barth; Akbey, Ümit; Oschkinat, Hartmut (Journal of Biomolecular NMR)

Accurate measurement of one-bond H–X heteronuclear dipolar couplings in MAS solid-state NMR - Schanda, Paul; Meier, Beat H.; Ernst, Matthias (Journal of Magnetic Resonance)
The accurate experimental determination of dipolar-coupling constants for one-bond heteronuclear dipolar couplings in solids is a key for the quantification of the amplitudes of motional processes. Averaging of the dipolar coupling reports on motions on time scales up to the inverse of the coupling constant, in our case tens of microseconds. Combining dipolar-coupling derived order parameters that characterize the amplitudes of the motion with relaxation data leads to a more precise characterization of the dynamical parameters and helps to disentangle the amplitudes and the time scales of the motional processes, which impact relaxation rates in a highly correlated way. Here. we describe and characterize an improved experimental protocol – based on REDOR – to measure these couplings in perdeuterated proteins with a reduced sensitivity to experimental missettings. Because such effects are presently the dominant source of systematic errors in experimental dipolar-coupling measurements, these compensated experiments should help to significantly improve the precision of such data. A detailed comparison with other commonly used pulse sequences (T-MREV, phase-inverted CP,R18 5/2, and R18 7/1) is provided.
Keywords: Nuclear and High Energy Physics; Biophysics; Biochemistry; Condensed Matter Physics

A proton-detected 4D solid-state NMR experiment for protein structure determination - Huber, Matthias; Hiller, Sebastian; Schanda, Paul; Ernst, Matthias; Böckmann, Anja; Verel, René; Meier, Beat H. (ChemPhysChem)
Adding a new dimension: 4D or 3D proton‐detected spectra of perdeuterated protein samples with 1H labelled amides and methyl groups permit collecting unambiguous distance restraints with high sensitivity and determining protein structure by solid‐state NMR (see picture).
Keywords: Physical and Theoretical Chemistry; Atomic and Molecular Physics; and Optics

Probing water accessibility in HET-s(218–289) amyloid fibrils by solid-state NMR - Van Melckebeke, Hélène; Schanda, Paul; Gath, Julia; Wasmer, Christian; Verel, René; Lange, Adam; Meier, Beat H.; Böckmann, Anja (Journal of Molecular Biology)
Despite the importance of protein fibrils in the context of conformational diseases, information on their structure is still sparse. Hydrogen/deuterium exchange measurements of backbone amide protons allow the identification hydrogen-bonding patterns and reveal pertinent information on the amyloid β-sheet architecture. However, they provide only little information on the identity of residues exposed to solvent or buried inside the fibril core. NMR spectroscopy is a potent method for identifying solvent-accessible residues in proteins via observation of polarization transfer between chemically exchanging side-chain protons and water protons. We show here that the combined use of highly deuterated samples and fast magic-angle spinning greatly attenuates unwanted spin diffusion and allows identification of polarization exchange with the solvent in a site-specific manner. We apply this measurement protocol to HET-s(218–289) prion fibrils under different conditions (including physiological pH, where protofibrils assemble together into thicker fibrils) and demonstrate that each protofibril of HET-s(218–289), is surrounded by water, thus excluding the existence of extended dry interfibril contacts. We also show that exchangeable side-chain protons inside the hydrophobic core of HET-s(218–289) do not exchange over time intervals of weeks to months. The experiments proposed in this study can provide insight into the detailed structural features of amyloid fibrils in general.

Destruction of invariant curves in the restricted circular planar three-body problem by using comparison of action - Galante, Joseph; Kaloshin, Vadim (Duke Mathematical Journal)
The classical principle of least action says that orbits of mechanical systems extremize action; an important subclass are those orbits that minimize action. In this paper we utilize this principle along with Aubry-Mather theory to construct (Birkhoff) regions of instability for a certain three-body problem, given by a Hamiltonian system of 2 degrees of freedom. We believe that these methods can be applied to construct instability regions for a variety of Hamiltonian systems with 2 degrees of freedom. The Hamiltonian model we consider describes dynamics of a Sun-Jupiter-comet system, and under some simplifying assumptions, we show the existence of instabilities for the orbit of the comet. In particular, we show that a comet which starts close to an orbit in the shape of an ellipse of eccentricity e=0.66 can increase in eccentricity up to e=0.96. In the sequels to this paper, we extend the result to beyond e=1 and show the existence of ejection orbits. Such orbits are initially well within the range of our solar system. This might give an indication of why most objects rotating around the Sun in our solar system have relatively low eccentricity.
Keywords: General Mathematics

Gene Dosage and Duplication - Fyodor Kondrashov (Evolution after Gene Duplication)

Acrocephalus orinus: A case of Mistaken identity - Koblik, Evgeniy A; Red'Kin, Yaroslav A; Meer, Margarita S; Derelle, Romain; Golenkina, Sofia A; Fyodor Kondrashov; Arkhipov, Vladimir Y (PLoS One)
Recent discovery of the Large-billed Reed Warbler (Acrocephalus orinus) in museums and in the wild significantly expanded our knowledge of its morphological traits and genetic variability, and revealed new data on geographical distribution of the breeding grounds, migration routes and wintering locations of this species. It is now certain that A. orinus is breeding in Central Asia; however, the precise area of distribution remains unclear. The difficulty in the further study of this species lies in the small number of known specimens, with only 13 currently available in museums, and in the relative uncertainty of the breeding area and habitat of this species. Following morphological and genetic analyses from Svensson, et al, we describe 14 new A. orinus specimens from collections of Zoological Museums of the former USSR from the territory of Central Asian states. All of these specimens were erroneously labeled as Blyth's Reed Warbler (A. dumetorum), which is thought to be a breeding species in these areas. The 14 new A. orinus specimens were collected during breeding season while most of the 85 A. dumetorum specimens from the same area were collected during the migration period. Our data indicate that the Central Asian territory previously attributed as breeding grounds of A. dumetorum is likely to constitute the breeding territory of A. orinus. This rare case of a re-description of the breeding territory of a lost species emphasizes the importance of maintenance of museum collections around the world. If the present data on the breeding grounds of A. orinus are confirmed with field observations and collections, the literature on the biology of A. dumetorum from the southern part of its range may have to be reconsidered.

Evidence of the harmonic Faraday instability in ultrasonic atomization experiments with a deep, inviscid fluid - Higginbotham, Andrew P; Guillen, A; Jones, Nick; Donnelly, Tom; Bernoff, Andrew (Journal of the Acoustical Society of America)
A popular method for generating micron-sized aerosols is to submerge ultrasonic (ω ∼ MHz) piezoelectric oscillators in a water bath. The submerged oscillator atomizes the fluid, creating droplets with radii proportional to the wavelength of the standing wave at the fluid surface. Classical theory for the Faraday instability predicts a parametric instability driving a capillary wave at the subharmonic (ω / 2) frequency. For many applications it is desirable to reduce the size of the droplets; however, using higher frequency oscillators becomes impractical beyond a few MHz. Observations are presented that demonstrate that smaller droplets may also be created by increasing the driving amplitude of the oscillator, and that this effect becomes more pronounced for large driving frequencies. It is shown that these observations are consistent with a transition from droplets associated with subharmonic (ω/2) capillary waves to harmonic (ω) capillary waves induced by larger driving frequencies and amplitudes, as predicted by a stability analysis of the capillary waves.

An energetic perspective on the regional response of precipitation to climate change - Muller, Caroline J; O’Gorman, P. A. (Nature Climate Change)
Understanding and predicting the response of the hydrological cycle to climate change is a major challenge with important societal implications. Much progress has been made in understanding the response of global average precipitation by considering the energy balances of the atmosphere and the surface1,2,3,4,5,6. This energetic perspective reveals that changes in temperature, greenhouse gases, aerosols, solar forcing and cloud feedbacks can all affect the global average rate of precipitation5,7,8,9,10,11. Local precipitation changes have conventionally been analysed using the water vapour budget, but here we show that the energetic approach can be extended to local changes in precipitation by including changes in horizontal energy transport. In simulations of twenty-first century climate change, this energy transport accounts for much of the spatial variability in precipitation change. We show that changes in radiative and surface sensible heat fluxes are a guide to the local precipitation response over land and at large scales, but not at small scales over the ocean, where cloud and water vapour radiative feedbacks dampen the response. The energetic approach described here helps bridge the gap between our understanding of global and regional precipitation changes. It could be applied to better understand the response of regional precipitation to different radiative forcings, including geo-engineering schemes, as well as to understand the differences between the fast and slow responses of regional precipitation to such forcings.

Intensification of precipitation extremes with warming in a cloud-resolving model - Muller, Caroline J; O’Gorman, Paul A.; Back, Larissa E. (Journal of Climate)
A cloud-resolving model is used to investigate the effect of warming on high percentiles of precipitation (precipitation extremes) in the idealized setting of radiative-convective equilibrium. While this idealized setting does not allow for several factors that influence precipitation in the tropics, it does allow for an evaluation of the response of precipitation extremes to warming in simulations with resolved rather than parameterized convection. The methodology developed should also be applicable to less idealized simulations. Modeled precipitation extremes are found to increase in magnitude in response to an increase in sea surface temperature. A dry static energy budget is used to relate the changes in precipitation extremes to changes in atmospheric temperature, vertical velocity, and precipitation efficiency. To first order, the changes in precipitation extremes are captured by changes in the mean temperature structure of the atmosphere. Changes in vertical velocities play a secondary role and tend to weaken the strength of precipitation extremes, despite an intensification of updraft velocities in the upper troposphere. The influence of changes in condensate transports on precipitation extremes is quantified in terms of a precipitation efficiency; it does not change greatly with warming. Tropical precipitation extremes have previously been found to increase at a greater fractional rate than the amount of atmospheric water vapor in observations of present-day variability and in some climate model simulations with parameterized convection. But the fractional increases in precipitation extremes in the cloud-resolving simulations are comparable in magnitude to those in surface water vapor concentrations (owing to a partial cancellation between dynamical and thermodynamical changes), and are substantially less than the fractional increases in column water vapor.
Keywords: Atmospheric Science

Instabilities of monolayered epithelia Shape and structure of villi and crypts - Hannezo, Edouard B; Prost, Jacques; Joanny, Jean (Physical Review Letters)
We study theoretically the shapes of a dividing epithelial monolayer of cells lying on top of an elastic stroma. The negative tension created by cell division provokes a buckling instability at a finite wave vector leading to the formation of periodic arrays of villi and crypts. The instability is similar to the buckling of a metallic plate under compression. We use the results to rationalize the various structures of the intestinal lining observed in vivo. Taking into account the coupling between cell division and local curvature, we obtain different patterns of villi and crypts, which could explain the different morphologies of the small intestine and the colon.

Glass-like dynamics of collective cell migration - Angelini, Thomas; Hannezo, Edouard B; Trepatc, Xavier; Marquez, Manuel; Fredberg, Jeffrey; Weitz, David (Proceedings of the National Academy of Sciences of the United States of America)
Collective cell migration in tissues occurs throughout embryonic development, during wound healing, and in cancerous tumor invasion, yet most detailed knowledge of cell migration comes from single-cell studies. As single cells migrate, the shape of the cell body fluctuates dramatically through cyclic processes of extension, adhesion, and retraction, accompanied by erratic changes in migration direction. Within confluent cell layers, such subcellular motions must be coupled between neighbors, yet the influence of these subcellular motions on collective migration is not known. Here we study motion within a confluent epithelial cell sheet, simultaneously measuring collective migration and subcellular motions, covering a broad range of length scales, time scales, and cell densities. At large length scales and time scales collective migration slows as cell density rises, yet the fastest cells move in large, multicell groups whose scale grows with increasing cell density. This behavior has an intriguing analogy to dynamic heterogeneities found in particulate systems as they become more crowded and approach a glass transition. In addition we find a diminishing self-diffusivity of short-wavelength motions within the cell layer, and growing peaks in the vibrational density of states associated with cooperative cell-shape fluctuations. Both of these observations are also intriguingly reminiscent of a glass transition. Thus, these results provide a broad and suggestive analogy between cell motion within a confluent layer and the dynamics of supercooled colloidal and molecular fluids approaching a glass transition.

Notch lineages and activity in intestinal stem cells determined by a new set of knock in mice - Fré, Silvia; Hannezo, Edouard B; Šale, Sanja; Huyghe, Mathilde; Lafkas, Daniel; Kissel, Holger; Louvi, Angeliki; Greve, Jeffrey; Louvard, Daniel; Artavanis Tsakonas, Spyros (PLoS One)
The conserved role of Notch signaling in controlling intestinal cell fate specification and homeostasis has been extensively studied. Nevertheless, the precise identity of the cells in which Notch signaling is active and the role of different Notch receptor paralogues in the intestine remain ambiguous, due to the lack of reliable tools to investigate Notch expression and function in vivo. We generated a new series of transgenic mice that allowed us, by lineage analysis, to formally prove that Notch1 and Notch2 are specifically expressed in crypt stem cells. In addition, a novel Notch reporter mouse, Hes1-EmGFP SAT, demonstrated exclusive Notch activity in crypt stem cells and absorptive progenitors. This roster of knock-in and reporter mice represents a valuable resource to functionally explore the Notch pathway in vivo in virtually all tissues.

Determination of iron sites and the amount of amorphization in radiation-damaged titanite (CaSiTiO5) - Salje, E K H; Safarik, D J; Taylor, R D; Pasternak, M P; Modic, Kimberly A; Groat, L A; Lashley, J C (Journal of Physics: Condensed Matter)
Iron is a ubiquitous impurity in metamict (radiation-damaged and partially amorphized) materials such as titanite (CaSiTiO5). Using 57Fe Mössbauer spectroscopy we find that iron in metamict titanite is partitioned between amorphous and crystalline regions based on valence. Trivalent iron exists in the crystalline titanite matrix whereas divalent iron exists almost exclusively in radiation-amorphized regions. We find that the relative abundances of the oxidation states correlate with the volume fraction of amorphous and crystalline regions. Our data also show that oxidation of iron proceeds along with the recrystallization of the amorphized regions. Recrystallization is confirmed to occur over the range 700 °C < T < 925 °C, and no further structural changes are observed at higher temperatures. It is surprising that our Mössbauer measurements show divalent iron to be surrounded by titanite with a high degree of short-range structural order in the amorphized regions. This observation is fundamentally different from other metamict materials such as zircon (ZrSiO4), where amorphized regions show no short-range order.

The effect of Ag concentration on the structural, electrical and thermal transport behavior of Pb:Te:Ag:Se mixtures and improvement of thermoelectric performance via Cu doping - Capps, J.; Ma, B.; Drye, T.; Nucklos, C.; Lindsey, S.; Rhodes, D.; Zhang, Q.; Modic, Kimberly A; Cawthorne, S.; Drymiotis, F. (Journal of Alloys and Compounds)
Pb, Te, Ag and Se, when reacted in a 1:1:x:1 (x = 1.9, 2.0, 2.01) molar ratio, form a two phase composite which consists of a phase which crystallizes in the fcc cubic PbSe structure and a phase that crystallizes in the Ag2Te structure. In this article, we demonstrate that by varying the Ag concentration, we can manipulate which variant of the Ag2Te structure stabilizes at room temperature (monoclinic α-Ag2Te or cubic β-Ag1.9Te) and can consequently manipulate the electrical and thermal transport behavior of the composite and hence the thermoelectric performance. Additionally, we show that Cu-doping results in an overall improvement in thermoelectric performance. Our results suggest that formation of composites is a viable path for achieving a phonon-glass-electron-crystal (PGEC) alloy.

Li–O2 and Li–S batteries with high energy storage - Bruce, Peter G.; Freunberger, Stefan Alexander; Hardwick, Laurence J.; Tarascon, Jean-Marie (Nature Materials)
Li-ion batteries have transformed portable electronics and will play a key role in the electrification of transport. However, the highest energy storage possible for Li-ion batteries is insufficient for the long-term needs of society, for example, extended-range electric vehicles. To go beyond the horizon of Li-ion batteries is a formidable challenge; there are few options. Here we consider two: Li–air (O2) and Li–S. The energy that can be stored in Li–air (based on aqueous or non-aqueous electrolytes) and Li–S cells is compared with Li-ion; the operation of the cells is discussed, as are the significant hurdles that will have to be overcome if such batteries are to succeed. Fundamental scientific advances in understanding the reactions occurring in the cells as well as new materials are key to overcoming these obstacles. The potential benefits of Li–air and Li–S justify the continued research effort that will be needed.

The Lithium-Oxygen battery with ether-based electrolytes - Freunberger, Stefan Alexander; Chen, Yuhui; Drewett, Nicholas E.; Hardwick, Laurence J.; Bardé, Fanny; Bruce, Peter G. (Angewandte Chemie International Edition)
The electrolyte is one of the greatest challenges facing the development of the non‐aqueous Li–O2 battery. Although ether‐based electrolytes do from Li2O2 on the first discharge, it is shown by various techniques that they also decompose and that decomposition increases while Li2O2 decreases on cycling (see picture). Thus, these electrolytes are not suitable.

Oxygen reactions in a non-aqueous Li+ electrolyte - Peng, Zhangquan; Freunberger, Stefan Alexander; Hardwick, Laurence J.; Chen, Yuhui; Giordani, Vincent; Bardé, Fanny; Novák, Petr; Graham, Duncan; Tarascon, Jean-Marie; Bruce, Peter G. (Angewandte Chemie International Edition)
Spectroscopic data (see picture) provide direct evidence that in non‐aqueous Li+ electrolyte, O2 is reduced to O2−, which then forms LiO2 on the electrode surface which disproportionates to Li2O2. On charging, Li2O2 decomposes directly, in a one‐step reaction to evolve O2 and does not pass through LiO2 as an intermediate.